2002
DOI: 10.1515/libr.2002.183
|View full text |Cite
|
Sign up to set email alerts
|

The Provision of Library and Information Services to Distance Learners: The Open University of Tanzania (OUT)

Abstract: This paper presents the findings of research conducted on the provision of information services to distance learners by the Open University of Tanzania (OUT). The objective of the research was to discover how the Open University of Tanzania provides library and information services to its distance learners and the extent to which these services meet the needs of the learners. The study was done with a view to suggesting ways in which information provision at OUT could be improved. Data collection was done in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 1 publication
0
8
0
Order By: Relevance
“…After the failure of the decision of Open University in Tanzania (OUT) not to provide direct library services to its students as reported by Mmari (1997), Msuya and Maro (2002) observe that OUT main library provides services to staff and students residing in Dar es Salam-the capital of Tanzania. Some books and other reading materials are placed at branches of the Tanzania Library Services (public library) for students living in those areas.…”
Section: Library and Information Services For Distance Learnersmentioning
confidence: 99%
“…After the failure of the decision of Open University in Tanzania (OUT) not to provide direct library services to its students as reported by Mmari (1997), Msuya and Maro (2002) observe that OUT main library provides services to staff and students residing in Dar es Salam-the capital of Tanzania. Some books and other reading materials are placed at branches of the Tanzania Library Services (public library) for students living in those areas.…”
Section: Library and Information Services For Distance Learnersmentioning
confidence: 99%
“…commonly myths associated with albinism are that an albino child is conceived when a woman has sexual intercourse during her menstruation; that a child with albinism is a ghost or a replacement or a substitute for a proper child by a deity or a spirit; and that a person with albinism is a curse from a god and/or the ancestral world (Richter et al 2017). There is a belief that the condition can also result from witchcraft or bad omen (Likumbo et al 2021;Richter et al 2017;Msuya 2002). Some of the misconceptions include the notion that albinos do not die but simply disappear, and that sex with a woman with albinism could cure infertility and AIDS (Clarke & Beale 2018).…”
Section: Albinism: Types Myths Misconceptions and Their Social Conditionmentioning
confidence: 99%
“…And finally, but not least, it is believed that albinism can be contagious. As a result, in places such as Tanzania, it is reported that some pregnant women refuse to shake hands with people with albinism or share utensils/dishes with them to avoid its transmission to their unborn children (Msuya 2002). In some African countries, albinism is believed to result from parents' wrongdoing; that is, it is contracted through behaviours that evoke social disapproval.…”
Section: Albinism: Types Myths Misconceptions and Their Social Conditionmentioning
confidence: 99%
“…As library services are crucial for distance students, lack of adequate library services may negatively affect them. In a study of library services for distance students in a Tanzanian university, deficient library and information services were indicated as one of the reasons that led many students to withdraw from their studies (Msuya and Maro, 2002).…”
Section: Literature Reviewmentioning
confidence: 99%